ANALISIS EFEKTIVITAS PENGGUNAAN APLIKASI MOBILE JKN DALAM MENINGKATKAN PELAYANAN BPJS KESEHATAN DI RSUD MALINGPING - Pamungkas, Ananda Fajar; Bangsawan, Try Adhi; Wajir, Dede Qodrat Al (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study was conducted to analyze the effectiveness of using the JKN mobile application and to identify the supporting and inhibiting factors in using the JKN mobile application in improving BPJS Kesehatan services at Malingping Regional General Hospital. This study used a descriptive qualitative research design. The results of this study indicate that the use of the JKN mobile application at Malingping Regional General Hospital has a positive impact in facilitating access to services, speeding up the service process, streamlining service time, reducing queues, and helping to ease the workload of service officers. However, several challenges were still found, such as limited digital literacy among the elderly, technical constraints in the application, and delays in doctor appointments that did not match the schedule. Nevertheless, there are supporting factors, including service officers who provide direct education to patients and service features on the application, including the use of the online queue feature. Overall, the use of Mobile JKN at Malingping Regional General Hospital is quite effective in improving BPJS Kesehatan services, but optimization is still needed, especially in terms of assisting elderly users, technological infrastructure, and coordination between the regional general hospital and doctors regarding service schedules.